INTERNAL AUDIT MODEL POST-ERP IMPLEMENTATION (ENTERPRISE RESOURCE PLANNING) AT PT XYZ - Damayanti, Mira; Chrismastuti, Agnes Advensia (KEUNIS, 2023)
The research aims to compare the audit process carried out after ERP implementation with the audit model using the 2019 COBIT framework in the Monitor, Evaluate and Assess domain. It is evaluating the effectiveness of the audit using COBIT 2019 compared to the audit currently being conducted at PT XYZ. This research is applied research, using a case study method and a qualitative approach. The object of this research is PT XYZ, a company distributing pipe and pump products. 2017 PT XYZ implemented an ERP system to replace the previous program. Data analysis with the steps applied compared to the current audit process carried out at PT XYZ with the 2019 COBIT-based audit using the Monitor, Evaluate, and Assess (MEA) approach and evaluated the effectiveness of the audit model using COBIT 2019, which can ensure that audit objectives in the ERP system can be achieved effectively. The result of the research shows that there are differences in the audit process that PT has carried out. XYZ after implementing ERP with an audit model using the COBIT 2019 framework. This difference can be affected by the time of system implementation. The audits using COBIT 2019 can be considered very effective compared to the previous audits conducted by PT XYZ. By using COBIT 2019, it can help PT XYZ in designing governance using several design factors that have been provided.